PHOTOMETRY AND BLAZHKO EFFECT IN RR Lyr TYPE STAR DM Cyg - Udovichenko, S. N.; Dubovsky, P. A.; Kudzej, I. (Одеські астрономічні публікації, 2010)
The photometric CCD observations for RR Lyr type star DM Cyg in Astronomical stations near Odessa(Ukraine) and Kolonica(Slovakia) in 2008 and near Odessa in 2009 have been carried out. The light curves in V system were obtained and the frequency Fourier analyse was performed. From Fourier spectra of the light curves 18 frequencies were identified. The weak Blazhko effect was detected.